Turkish Journalists' Attitudes, Perceived Constraints, and Knowledge about AI in Journalism - Semra Demirdiş (Yeni Medya)
This study examines Turkish journalists' attitudes towards the integration of artificial intelligence (AI) in journalism, highlighting both opportunities and various challenges. The findings support the view that AI can enhance efficiency in areas such as data analysis and content personalization, while also emphasising significant concerns related to job security, editorial independence, and data reliability. In the context of Turkey's economic and digital infrastructure limitations, journalists’ cautious approach to AI appears shaped by limited resources and training opportunities. The study aims to understand Turkish journalists' perspectives on AI applications, identify perceived obstacles, and evaluate the potential impacts of this technology on journalism. The research employs a quantitative method with a survey administered to 350 journalists working in various media fields. Findings indicate that while journalists recognize the benefits of AI, their optimism is balanced by concerns over job loss and threats to professional values. The results suggest the need to address structural barriers to AI adoption in the Turkish media sector, with recommendations for targeted training programs and reliable digital infrastructure. This study contributes valuable insights into the effects of AI on journalism in Türkiye, providing findings that may be adapted to broader media contexts.